Continuity despite change : the politics of labor regulation in Latin America - Carnes, Matthew E., 1970- (Social science history., 2014)
Matthew Carnes explains why Latin America's pattern of protective labour regulation has been surprisingly resistant to fundamental reform over the course of the last century, especially during the period of intense pressure from globalisation. He develops a theory based on two factors - the skill distribution in the economy and the organisational capacity of labour - to explain the remarkable continuity in national-level labour codes.